Distribution of Glycoconjugates in the Gills of Oscar Fish (Astronotus ocellatus) - Mustafa Öztop; Kenan Çınar; Emel Demirbağ (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2021)
Glycoconjugates involved in many functions are produced by many cell types. This study aimed to investigate the glycoconjugate expression in the Oscar fish (Astronotus ocellatus) gills using five horseradish peroxidase-conjugated lectins. This study revealed that gill epithelial cells react with Canavalia ensiformis agglutinin (Con A) and Arachis hypogaea agglutinin (PNA). Strong reaction to Con A was seen in the epithelial cells of the gill primary lamellae. Epithelial cells of primary and secondary lamellae and eosinophilic granular cells had varying intensity of PNA binding. Ulex europaeus agglutinin-I(UEA-I) positive eosinophilic granular cells were observed in the connective tissue of primary lamellae. Epithelial cells of the gill primary filament had Con A reaction in varying intensities. Superficial epithelial cells reacted with PNA in various degrees. Epithelial cells of the secondary lamellae had Con A and PNA positive reaction. These results indicate that glycoconjugate distribution may show interspecific variations, suggesting that the high heterogeneity of naturally occurring glycoconjugates in the epithelial cells of Oscar fish gills might be attributed to the various functional roles of glycoconjugates.